2005
DOI: 10.1111/j.1365-2427.2005.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and biomass of heterotrophic microorganisms in Lake Tanganyika

Abstract: 1. This study focused on heterotrophic microorganisms in the two main basins (north and south) of Lake Tanganyika during dry and wet seasons in 2002. Bacteria (81% cocci) were abundant (2.28-5.30 · 10 6 cells mL )1 ). During the dry season, in the south basin, bacterial biomass reached a maximum of 2.27 g C m )2 and phytoplankton biomass was 3.75 g C m )2 (integrated over a water column of 100 m). 2. Protozoan abundance was constituted of 99% of heterotrophic nanoflagellates (HNF). Communities of flagellates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 59 publications
(109 reference statements)
2
40
0
1
Order By: Relevance
“…To date, only few studies reported abundance and production of picoplankton in East African Great lakes (Pirlot et al 2005 ;Sarmento et al 2008 ;Stenuite et al 2009a, b ) . Sarmento et al ( 2008 ) reported the fi rst data on bacterial abundances in Lake Kivu.…”
Section: Prokaryotic Cell Abundances Biomass and Productionmentioning
confidence: 99%
“…To date, only few studies reported abundance and production of picoplankton in East African Great lakes (Pirlot et al 2005 ;Sarmento et al 2008 ;Stenuite et al 2009a, b ) . Sarmento et al ( 2008 ) reported the fi rst data on bacterial abundances in Lake Kivu.…”
Section: Prokaryotic Cell Abundances Biomass and Productionmentioning
confidence: 99%
“…Além disso, várias espécies de ciliados e flagelados são capazes de consumir algas, cianobactérias e outros protozoários, tendo funções semelhantes às dos organismos metazoários (Sherr & Sherr 1994). Eles podem também aumentar a produção primária em ambientes dominados por protozoários mixotróficos (Pirlot et al 2005) e influenciar o "pool" de matéria orgânica dissolvida, de vírus e de outras partículas de tamanho viral nos ambientes aquáticos, uma vez que alguns protozoários flagelados podem se alimentar destes componentes (Tranvik et al 1993, González & Suttle 1993.…”
Section: Introductionunclassified
“…viride nearly equaled or exceeded the phytoplankton biomass during much of the stably stratified period; this protozoan probably has a symbiotic relationship with zoochlorellae, which were always present in it' (Hecky & Kling 1981, p. 548). More recently, ciliates are still found to be an abundant group in the lake (Descy et al 2005) and in 2002, total autotrophic carbon was partly sustained by the endosymbionts in Strombidium (Pirlot et al 2005). When fixed phytoplankton samples were processed during the same study of Lake Tanganyika, it was observed that this abundant ciliate contained numerous coccoid green algal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable role of ciliates is especially valid for the ancient, large tropical oligotrophic Lake Tanganyika (Hecky & Kling 1981, 1987Pirlot et al 2005). There 'the biomass of Strombidium cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation